Special paper Treatment of cutaneous warts induced by human papillomaviruses (HPV) - Goyal-Stec, Manjari; Majewski, Sławomir (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2006)
Cutaneous warts are one of the most common dermatological problems in children and adolescents. Common warts, plantar warts and plane warts are proliferative lesions due to local infection with some types of human papillomaviruses (HPV). Treatment of cutaneous warts is focused on improving the quality of life of patients and on preventing spread of the infection in the population. A review of the results of randomized studies, performed according to evidence-based medicine, indicates that there is no single therapeutic compound or method completely effective for treatment of cutaneous warts. It is to be stressed that long-term observational studies have shown up to 40% spontaneous remission of cutaneous warts (due to local and systemic immune responses activated upon HPV infection and responsible for wart rejection). The importance of the immune system is best illustrated by findings in immunosuppresed individuals in whom there is a high prevalence of various cutaneous lesions induced by HPV (both benign keratotic warts and premalignant and malignant lesions). The high efficacy of preparations containing salicylic acid (also compound formulas) argues for their use as a first-line therapy of cutaneous warts. Second-line therapies include: cryotherapy, laser therapy pharmacotherapy (e.g. 5-fluorouracil, bleomycin, retinoids) and immunotherapy. In case of no response to salicylic acid or cryotherpapy patients should be referred to a dermatologist and treatments should be individualized. In the article we review data on epidemiology of cutaneous warts and on various treatment modalities.